Effects of Multimedia Video Projection on Undergraduate Students’ Achievement and Retention in Quantitative Economics in the Universities in Gombe State, Nigeria - Egboka, Patience; H. Dalhatu, Aliyu,; Dahiru, Ahmed,; Tukur, 4Muntaka, (Kashere Journal of Education, 2021)
This study was design to determine the effects of multimedia video projection on undergraduates’ students’ achievement and retention in quantitative Economics in Universities in Gombe State, Nigeria. Three research questions and two null hypotheses guided the study. Quasi-experimental research design specifying pretest posttest control group design was adopted for the study. The study was conducted in Federal University Kashere and Gombe State University, Gombe. Quantitative Economics Achievement Test (QEAT) designed by the researcher and validated three experts from Federal University, Kashere, Gombe State was the instrument used for the data collected for the study. The reliability coefficient of the instrument was determined to be 0.74 through Kudder Richardson 20 (KR-20) statistics. Mean and standard deviation were used to answer research questions; while Analysis of Covariance was used to test the null hypotheses at 0.05 level of significance. The findings of the study revealed that multimedia projection approach is more efficacious in enhancing students’ achievement and retention in quantitative Economics than lecture method. There is no statically significant difference in achievement in Quantitative Economics by male and female students who were taught using multimedia video projection approach. Based on the findings, it was recommended that the use of multimedia projection should be encouraged in teaching quantitative economics in tertiary institutions and that is use should be popularized through workshops, seminars, and conferences.